Efektivitas Penerapan Pembelajaran Online Pada Masa Covid-19 Terhadap Motivasi dan Keaktifan Belajar Mahasiswa - Satria Evans Umboh; Hapyvania Tenda (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
The Covid 19 pandemic is a health problem caused by a virus, the Covid 19 virus greatly affects all human activities including education. With this virus, many educational institutions are conducting or implementing distance learning using online learning models. Online learning is an alternative to implementing the teaching and learning process so that students continue to learn even online between educators and students. The purpose of writing this study is to find out how effective the application of online learning at STT IKAT is. This research uses direct action research methods by observing, interviewing and reading several book sources. So from this study it was found that the application of online learning in every educational institution is needed to support the learning process. And also educational institutions can take advantage of technological developments that are increasingly developing. Students must try to be active and motivated to learn amid the Covid-19 pandemic.